2019
DOI: 10.1016/j.conbuildmat.2018.11.144
|View full text |Cite
|
Sign up to set email alerts
|

Temperature related pull-out performance of chemical anchor bolts in fibre concrete

Abstract: Anchor bolts are often fixed into a concrete soffit of structures and they are used in ambient and cold store locations. The chemical anchor bolt relies purely on the tensile strength of the concrete to carry the imposed load, assuming the bond strength of the resin is greater than the tensile strength of the concrete. The properties of concrete are changed by the addition of both steel and polypropylene fibres. This paper investigates the relative performance of each fibre type with regard to initial and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Therefore, non-linear Drucker-Prager's yield function which improves linear Drucker-Prager's equation is applied in this study. Non-linear Drucker-Prager yield function applied in this research is represented by the following Equation (7).…”
Section: Overview Of Crack Growth Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, non-linear Drucker-Prager's yield function which improves linear Drucker-Prager's equation is applied in this study. Non-linear Drucker-Prager yield function applied in this research is represented by the following Equation (7).…”
Section: Overview Of Crack Growth Analysismentioning
confidence: 99%
“…Under these backgrounds, many researchers have already conducted the research on the pull-out fracture of anchor bolts. For example, there are experimental studies [5,[7][8][9], some of them focusing on the damage of the base concrete [10,11], and others focusing on the bond fracture between concrete and anchor bolt [12,13], and studies focusing on the long-term strength against aging performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that the reinforcements placed in the same spot as the installed anchors, had the direct impact on the axial tensile capacity (19). There are also other studies that use the temperature as a variable (20)(21)(22). Also, examined by empirical observation, the concrete edge failure of the single and group anchors, after fi re exposure by Tian et al (23).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that with increasing edge distance, concrete edges become more resistant to failure. Richardson et al, [ 32 ] Nilforoush et al, [ 33 ] and Kocur et al [ 34 ] conducted tests on steel and synthetic fiber concrete. Concrete edge failure was observed in most of the tests.…”
Section: Introductionmentioning
confidence: 99%